Crystalline Structure, Optical Properties and Photocatalytic Activity of Cr3+-Doped ZnO Nanoparticles - Nguyen Xuan, Sang; Minh Quan, Nguyen; Huu Tho, Nguyen; Thi Thanh Thuy Mai, Le; Van Cuu, Ho (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4750, 2018)
Abstract: In this work, nanocrystal Cr 3+ -doped ZnO was successfully fabricated by the solgel method. Although X-ray diffraction patterns showed no other secondary phase in Cr 3+ -doped ZnO samples, the lattice constants (a and c) decreased slightly in comparison to those of pure ZnO samples. The photoluminescence emission intensity of the doped sample was dramatically reduced, which indicated that the reduction of the radiative recombination rate. The photocatalytic degradation activity of methylene blue materials was investigated and showed that, in the presence of doped metal ions, the photocatalytic activity of ZnO was improved. The reason of enhanced photocatalytic activity was tentatively determined and clarified. Keywords: ZnO nanocrystal, solgel, photocatalytic ability, doped semiconductor. References [1] M. Vaseem, A. Umar, and Y. Hahn, "ZnO Nanoparticles : Growth , Properties , and Applications", Metal Oxide Nanostructures and Their Applications,Vol. 5.pp. 1-36, 1988. [2] B. Wang et al., “Effects of Cr-doping on the photoluminescence and ferromagnetism at room temperature in ZnO nanomaterials prepared by soft chemistry route,” Mater. Chem. Phys., Vol. 113, No. 1, pp. 103–106, 2009. [3] R. Velmurugan and M. Swaminathan, “An efficient nanostructured ZnO for dye sensitized degradation of Reactive Red 120 dye under solar light,” Sol. Energy Mater. Sol. Cells, Vol. 95, No. 3, pp. 942–950, 2011. [4] M. Pirhashemi, A. Habibi-Yangjeh, and S. Rahim Pouran, “Review on the criteria anticipated for the fabrication of highly efficient ZnO-based visible-light-driven photocatalysts,” J. Ind. Eng. Chem., Vol. 62, pp. 1–25, 2018. [5] T. A. Abdel-Baset, Y.-W. Fang, B. Anis, C.-G. Duan, and M. Abdel-Hafiez, “Structural and Magnetic Properties of Transition-Metal-Doped Zn1−x FexO” Nanoscale Res. Lett., Vol. 11, No. 1, p. 115-128, 2016. [6] K. Irshad, M. T. Khan, and A. Murtaza, “Synthesis and characterization of transition-metals-doped ZnO nanoparticles by sol-gel auto-combustion method,” Phys. B Condens. Matter, Vol. 543, May, pp. 1–6, 2018. [7] D. Chu, Y. P. Zeng, and D. Jiang, “Synthesis and growth mechanism of Cr-doped ZnO single-crystalline nanowires,” Solid State Commun., Vol. 143, No. 6–7, pp. 308–312, 2007. [8] S. Wang et al., “Effects of Temperature on the Microstructure and Magnetic Property of Cr-Doped ZnO DMS Prepared by Hydrothermal Route Assisted by Pulsed Magnetic Fields”,J. Chem., Vol. 2013, pp. 7-14, 2013. [9] Y. Liu et al., “Effects of Cr-doping on the optical and magnetic properties in ZnO nanoparticles prepared by sol-gel method”, J. Alloys Compd., Vol. 486, No. 1–2, pp. 835–838, 2009. [10] L. Znaidi, “Sol-gel-deposited ZnO thin films: A review,” Mater. Sci. Eng. B Solid-State Mater. Adv. Technol., Vol. 174, No. 1–3, pp. 18–30, 2010. [11] L. Schneider et al., “Fabrication and analysis of Cr-doped ZnO nanoparticles from the gas phase,” Nanotechnology, Vol. 20, No. 13, pp. 135604. 2009. [12] M. R. Iskandar, E. Saepuloh, L. Safriani, and A. Bahtiar, “Optical and structural properties of zinc oxide nanorod synthesized by sol-gel method,” AIP Confer. Proceed., Vol. 143, pp. 143–146, 2013. [13] Y. Li et al., “Structure and magnetic properties of Cr-doped ZnO nanoparticles prepared under high magnetic field,” Solid State Commun., Vol. 150, No. 15–16, pp. 751–754, 2010. [14] T. A. Abdel-Baset, Y. W. Fang, C. G. Duan, and M. Abdel-Hafiez, “Magnetic Properties of Chromium-Doped ZnO”,J. Supercond. Nov. Magn., Vol. 29, No. 7, pp. 1937–1942, 2016. [15] A. Jiménez-González, “Optical and electrical characteristics of aluminum-doped ZnO thin films prepared by solgel technique,” J. Cryst. Growth, Vol. 192, No. 3–4, pp. 430–438, 1998. [16] Z. N. Kayani, M. Siddiq, S. Riaz, and S. Naseem, “Optical, magnetic and structural properties of Cr-doped ZnO thin films by sol-gel dip-coating method,” Mater. Res. Express, Vol. 4, No. 9, pp. 096403. 2017. [17] P. Kaur, S. Kumar, N. S. Negi, and S. M. Rao, “Enhanced magnetism in Cr-doped ZnO nanoparticles with nitrogen co-doping synthesized using sol–gel technique,” Appl. Nanosci., Vol. 5, No. 3, pp. 367–372, 2015. [18] N. Iqbal, I. Khan, Z. H. A. Yamani, and A. Qurashi, “A facile one-step strategy for in-situ fabrication of WO 3 -BiVO 4 nanoarrays for solar-driven photoelectrochemical water splitting applications,” Sol. Energy, Vol. 144, pp. 604–611, 2017. [19] S. Bagheri, K. Shameli, and S. B. Abd Hamid, “Synthesis and characterization of anatase titanium dioxide nanoparticles using egg white solution via Sol-Gel method,” J. Chem., vol. 2013,pp. 848205. 2013. [20] S. Senthilkumaar, K. Rajendran, S. Banerjee, T. K. Chini, and V. Sengodan, “Influence of Mn doping on the microstructure and optical property of ZnO,” Mater. Sci. Semicond. Process., Vol. 11, No. 1, pp. 6–12, 2008. [21] A. Houas, “Photocatalytic degradation pathway of methylene blue in water,” Appl. Catal. B Environ., Vol. 31, No. 2, pp. 145–157, 2001. [22] M. Wang, Y. Zhou, Y. Zhang, E. Jung Kim, S. Hong Hahn, and S. Gie Seong, “Near-infrared photoluminescence from ZnO,” Appl. Phys. Lett., Vol. 100, No. 10, pp. 19–23, 2012. [23] A. Janotti and C. G. Van De Walle, “Fundamentals of zinc oxide as a semiconductor,” Reports Prog. Phys., Vol. 72, No. 12, pp. 126501, 2009. [24] Q. Qi, T. Zhang, L. Liu, X. Zheng, and G. Lu, “Improved NH3, C2H5OH, and CH3COCH3sensing properties of SnO2nanofibers by adding block copolymer P123” Sensors Actuators, B Chem., Vol. 141, No. 1, pp. 174–178, 2009. [25] S. Repp and E. Erdem, “Controlling the exciton energy of zinc oxide (ZnO) quantum dots by changing the confinement conditions,” Spectrochim. Acta - Part A Mol. Biomol. Spectrosc., Vol. 152, pp. 637–644, 2016. [26] U. Ilyas et al., “Temperature-dependent stoichiometric alteration in ZnO:Mn nanostructured thin films for enhanced ferromagnetic response,” Appl. Surf. Sci., Vol. 387, pp. 461–468, 2016. [27] A. Houas, “Photocatalytic degradation pathway of methylene blue in water”, Applied Catalysis B: Environmental, Vol. 31, No. 2, pp. 145–157, 2001. [28] R. Velmurugan, M. Swaminathan, “An efficient nanostructured ZnO for dye sensitized degradation of Reactive Red 120 dye under solar light”, Solar Energy Materials and Solar Cells, vol. 95, No. 3, pp 942–950, 2011. [29] N. F. Djaja, A. Noorhidayati, R. Saleh, “Synthesis, physical properties and catalytic activity of Cr-doped ZnO nanoparticles”, Vol. 30028, pp.30028, 2016. [30] W. Li, G. Wang, C. Chen, J. Liao, Z. Li, “Enhanced Visible Light Photocatalytic Activity of ZnO Nanowires Doped with Mn2+ and Co2+ Ions”, Nanomaterials, Vol 7, No. 1, pp. 20-31, 2017.